2007
DOI: 10.1074/jbc.m610778200
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Hydrochloride Specifically Inhibits COX-2 by Preventing COX-2 N-Glycosylation and by Increasing COX-2 Protein Turnover in a Proteasome-dependent Manner

Abstract: COX-2 and its products, including prostaglandin E 2 , are involved in many inflammatory processes. Glucosamine (GS) is an amino monosaccharide and has been widely used for alternative regimen of (osteo)arthritis. However, the mechanism of action of GS on COX-2 expression remains unclear. Here we describe a new action mechanism of glucosamine hydrochloride (GS-HCl) to tackle endogenous and agonistdriven COX-2 at protein level. GS-HCl (but not GS sulfate, N-acetyl GS, or galactosamine HCl) resulted in a shift in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 35 publications
5
45
2
1
Order By: Relevance
“…We, as well as others have previously reported that COX-2 expression is regulated at the post-transcriptional (mRNA stability) and/or translational (protein turnover) levels (35,(42)(43)(44). In the present study, however, experiments using Act D and CHX revealed that PDN did not affect the mRNA and protein stability of COX-2 in the IL-1β-treated HEI-OC1 cells (Fig.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…We, as well as others have previously reported that COX-2 expression is regulated at the post-transcriptional (mRNA stability) and/or translational (protein turnover) levels (35,(42)(43)(44). In the present study, however, experiments using Act D and CHX revealed that PDN did not affect the mRNA and protein stability of COX-2 in the IL-1β-treated HEI-OC1 cells (Fig.…”
Section: Discussioncontrasting
confidence: 43%
“…AP-1 is another transcription factor that binds to AP-1 cis-acting element and stimulates COX-2 transcription (31), and its activation is largely dependent on the activity of upstream signaling effectors, such as ERK-1/2 and JNK-1/2 (32,33). It has been demonstrated that treatment with IL-1β induces the phosphorylation of MAPKs (ERK-1/2, JNK-1/2 and p38 MAPK) and the IκB-α proteolysisdependent activation of NF-κB, and their activation is critical for the cytokine-mediated induction of COX-2 expression in various types of cells (29)(30)(31)34,35). Of note, has also been demonstrated that treatment with IL-1β (1 ng/ml) for 15 min increases the phosphorylation of ERK-1/2 and JNK-1/2, but not that of p38 MAPK in HEI-OC1 cells (36).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucosamine (GS) has been well established as a substitutable medical drug for rheumatoid arthritis or osteoarthritis (Reginster et al, 2001;Hua et al, 2005). Previous studies have demonstrated that GS regulates expression of COX-2 and production of PGE2 via IL-1β treatment in A549 human lung epithelial cells (Jang et al, 2007). Also, GS reduced IL-1β induced COX-2 expression at both transcriptional and translational levels in chondrocytes and synoviocytes (Nakamura et al, 2004).…”
Section: Discussionmentioning
confidence: 99%